Crypt apoptotic body counts in normal ileal biopsies overlap with graft-versus-host disease and acute cellular rejection of small bowel allografts - Sung, Diana; Iuga, Alina C.; Kato, Tomoaki; Martinez, Mercedes; Remotti, Helen E.; Lagana, Stephen M. (Human pathology, 2016)
Crypt apoptosis in intestinal epithelium is an important diagnostic feature of graft-versus-host disease (GVHD) and acute cellular rejection (ACR) of intestinal transplants (ITx). In ITx pathology, 2 or fewer apoptotic bodies in 10 consecutive crypts are considered normal, whereas 6 or more is consistent with mild ACR. The presence of 3 to 5 apoptotic bodies is problematic and is often classified as indeterminate for ACR. The minimum diagnostic threshold for GVHD is controversial but also depends on the apoptotic body count (ABC). We investigated how many crypt apoptotic bodies could be identified in histologically normal ileal biopsies from healthy subjects (native intestines, no bone marrow transplant) who underwent screening colonoscopy and had ileal biopsy to confirm complete colonoscopy. We recorded the number of biopsy pieces per specimen and the maximum ABC in 10 consecutive crypts. Twenty-six of 40 patients (65%) had an ABC of 3 or more in 10 crypts, thus only 35% were “normal.” Four (10%) had an ABC of ≥6 (positive for ACR). Twenty-two (55%) had 3–5 (indefinite for ACR). Depending on the criteria, up to 60% of the cases could be diagnosed as positive for GVHD.